Penyelesaian Perkara Anak yang Berhadapan dengan Hukum Menurut Undang-Undang No. 11 Tahun 2012 - Rachmawati, Rachmawati (Tadabbur: Jurnal Peradaban Islam, 2020)
The repressive juvenile justice paradigm has begun to be abandoned and replaced by the concept of solving a child criminal case with a restorative concept that views all parties, perpetrators, victims, and communities having equal opportunity to resolve conflicts caused by a crime. The restorative concept is in conformity with the conventions agreed upon by countries in the world in the Convention on the rights of the child in 1990 with international instruments including Beijing Rule dated 29 November 1985. The study of the crime against children in Islam has existed before the rule of the child in the ancient conventional low. The objective of punishment in Islam is not only to recognize the retributive objectives as the main objective in criminal prosecution but also to recognize other objectives such as the rehabilitation of the perpetrator and also the restorative between the perpetrator and the victim. Here is the interesting thing that will be studied comprehensively related Maqasid Al Syari’ah in applying restorative justice especially in case of child face to law. See the complexity that accompanied restorative justice in children facing the law, the authors are interested to examine the settlement of lawsuits children in accordance with the law no 11 of 2012 analysis Maqasid Al syari’ah this research is library research, descriptive analysis and analyze data qualitative with inductive method. The approach used is normative juridical, by looking at restorative justice in the penal law of Indonesia, this research aims to know the value of Maqasid Al Syari’ah in process of settlement of child crime case and examining view of Islam law to restorative justice value contained in law no 11 of 2012. After the research, it can be conclude that the application of restorative justice has long been adopted in the Islamic legal system, precisely on qiyas-diyat criminal acts. In the context of children, the application of restorative justice is more accommodated, given the urgency and for the benefit of the child as the nation’s successor. Whereas in viewing restorative justice in the SPPA act indicates the existence of reconciliation effort of forgiveness, correction of relationship, there is also structural responsibility as balancing individual responsibility, all of which obviously accommodated in the purpose of punishment Al-isti’adah.